Comparative analysis of Rhipicephalus microplus (Canestrini, 1888) infestation in pure breed (Hereford) and cross breed (Braford) cattle herds subjected to the same chemical treatments - Morel, Nicolas; Torrents, Jorgelina; Nava, Santiago (Springer Nature, 2024)
The aim of this work was to analyze the R. microplus (Canestrini, 1888) infestation in two bovine herds with different degrees of natural resistance (i.e., Hereford and Braford) to ticks subjected to an identical chemical treatment scheme to ticks at the same farm, to demonstrate the impact on tick control of the incorporation of a more resistant bovine breed. Two groups of ten Hereford and Braford cows each were subjected to eleven chemical treatments between August 2022 and October 2023 (four fluazuron, two fipronil 1%, one ivermectin 3.15% and four immersion in a dipping vat with a combination of cypermethrin 10% and ethion 40%). Tick population was shown to be susceptible to ivermectin, fluazuron and the mix cypermethrin 10%-ethion 40% and resistant to fipronil according to in vitro tests. Tick infestation was significantly greater in the Hereford cows than in the Braford cows. Tick infestation in both Hereford and Braford breeds was similar when treatment with functional drugs was applied, but when a block of the treatments was done with drugs with decreased functionality due to resistance (i.e. fipronil), treatment failure was manifested more strongly in the most susceptible breed. The incorporation of cattle breeds with moderate or high resistance to R. microplus is instrumental to optimize the efficacy and sustainability of chemical control of ticks in a scenario where resistance to one or more chemical groups is almost ubiquitous, because it favors the biological control of this parasite.